A joalheria no acervo do Museu de Arte Sacra de São Paulo - Benutti, Maria Antonia [UNESP]; Müller, Bruno [UNESP] (My University, 2013)
The jewels, be they used as decorations or some other specific function, are carriers of meaning, representatives of groups, peoples, territories or historical moments. In preliminary studies on the history of Brazilian jewelry, and the recent ascendancy of Brazil in the jewelry market, this research seeks to delve into the history of the production of religious jewelry from São Paulo in the Brazilian colonial period, through the collection of the São Paulo Museum of Sacred Art. This study aims to analyze the museum's collection of jewelry, in two respects: the pieces of jewelry and its pictorial representation in works of art.
Keywords: Brazilian jewelry; History of art; Jewel design; Jewelry